Blockchain-based event processing in supply chains—A case study at IKEA. (October 2020) - Sund, Tobias; Lööf, Claes; Nadjm-Tehrani, Simin; Asplund, Mikael
Highlights: Event processing for traceability in supply chains require significant capacity. Blockchains are maturing and provide many benefits for implementing traceability in supply chains. Current technologies need to further improve to match processing requirements for large-scale traceability management. Abstract: One of the major areas of interest for deployment of blockchains is in the supply chain sector where decentralisation combined with immutability is expected to enhance the transparency and robustness of transaction processing drastically. In this work we contribute to a feasibility study for permissioned blockchains in the context of a major international retail company. First, we characterise the types, relationships, and volumes of events that are created in the life cycle of a product from creation to ownership transfer. We use the created event model and the data from the company operations to identify the load that such an event processing system would have to manage. Then we create a prototype based on Quorum that deals with a significant subset of the events and expose the blockchain-based prototype to variations in load to identify the maximum throughput and average transaction processing time. This system can then form the basis of understanding the bottlenecks, configuration settings and platform choices needed in future potential deployment.